Biblical theology and missiological education in Asia: essays in honour of the Rev. Dr. Brian C. Wintle - Chrispal, Ashish; Raj, Paul Mohan; Arles, Siga; Wintle, Brian Charles (Studies in the gospel interface with Indian contexts, 2011)
Brian Charles Wintle, b. 1944, British born Indian theologist; contributed articles